Move, eat, sleep, repeat: Living by rhythm with proactive self-tracking technologies - Vigren Minna; Bergroth Harley (Sciendo, 2022)
Proactive self-tracking is a proliferating digital media practice that involves gathering data about the body and the self outside a clinical healthcare setting. Various studies have noted that self-tracking technologies affect people's everyday modes of thought and action and stick to their lifeworlds because these technologies seek to promote “improved” modes of behaviour. We investigate how the specific devices and interfaces involved in self-tracking attract and prescribe rhythmicity into everyday lives and elaborate on how human bodies and technical systems of self-tracking interact rhythmically. We draw from new materialist ontology, combining it with Henri Lefebvre's method of rhythmanalysis and his notion of dressage. We employ a collaborative autoethnographical approach and engage with both of our personal fieldwork experiences in living with self-tracking devices. We argue that rhythmicity and dressage are fruitful analytical tools to use in understanding human–technology attachments as well as a variety of everyday struggles inherent in self-tracking practices.